Review of competency-based models and quality standards in training and education in the addiction field. - Nováková, Elizabeth; Volfová, Anna; Miovský, Michal; Lososová, Amalie (Journal of Substance Use, 2025)
Background: A competent workforce is needed to face the global problem of substance use. Competencies are composed of knowledge, abilities and skills. The aim was to map the competency-based models and quality standards in education and training. Methods: The papers for the scoping review were obtained by a systematic search of scientific databases, complemented by the gray literature. The 43 papers were examined fully. Papers focusing on medical doctors, nurses, and social work were excluded. The results consist of the information from 19 sources that have been analyzed and clustered according to their main focus. Results: Experts emphasize the need to establish core competencies. Areas such as assessment, early detection, referral and empathic communication are emerging. Competency-based education is becoming popular for many reasons: to produce globally competitive graduates, to achieve quality and foster deeper learning, and to create a system for the continuous improvement. For the implementation of competency-based education, the cooperation of stakeholders is crucial as well as capacity building. Conclusions: The results show heterogeneity in terms of competencies, curricula, and standards. The paper responds to gaps and highlights missing standardization processes and implementation practices and emphasizes the importance of international collaboration, support, and networking.